2001
DOI: 10.1046/j.1365-2133.2001.04479.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple idiopathic mucocutaneous neuromas: a new entity?.

Abstract: We report a 53-year-old woman who presented with multiple painful red cutaneous papules that had been growing slowly for 13 years. Histopathology showed typical features of neuroma. Biological, morphological and genetic investigations were negative and excluded the diagnosis of multiple endocrine neoplasia type 2b. After reviewing the literature, we concluded that our patient has an extremely unusual acquired disease, which must be considered as a distinct entity in the spectrum of cutaneous neurological disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 9 publications
2
21
1
Order By: Relevance
“…Some of these occurred in patients with features of MEN while others occurred in the absence of other syndromic features (Table I). [5][6][7][8][9] Histologically, PENs are characterized by a proliferation of delicate spindled cells in the upper dermis distributed in distinct fascicles, which can be separated by clear clefts. The spindled nuclei often have a palisaded appearance.…”
Section: Multiple Palisaded Encapsulated Neuromas In a Child Without mentioning
confidence: 99%
“…Some of these occurred in patients with features of MEN while others occurred in the absence of other syndromic features (Table I). [5][6][7][8][9] Histologically, PENs are characterized by a proliferation of delicate spindled cells in the upper dermis distributed in distinct fascicles, which can be separated by clear clefts. The spindled nuclei often have a palisaded appearance.…”
Section: Multiple Palisaded Encapsulated Neuromas In a Child Without mentioning
confidence: 99%
“…29 A point mutation in the RET proto-oncogene in exons 10,11,13,14,15, and 16 (codon 918) has been observed in MEN 2 syndrome. 7,30 In MEN 2B, clinical evidence of MTC usually becomes apparent in adolescence but has also been reported in childhood. 31 Mucosal neuromas occur at an early age, typically before the presentation of MTC and phaeochromocytoma.…”
Section: Discussionmentioning
confidence: 96%
“…The diagnosis of MEN 2B was excluded with morphological and mutational analysis including the exons 15 and 16 of the RET protooncogene in this case, and the authors concluded that multiple idiopathic mucocutaneous neuromas might be a new entity. 7 MTCs arise from parafollicular C cells that secrete calcitonin. It is a potentially lethal neoplasm occurring sporadically (in 75% of cases) or in an autosomal dominant familial pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50,74,[77][78][79][80]82 In 4 affected families, genetic analysis confirmed the absence of mutations in the RET protooncogene. 69,[79][80][81] We postulate that some of these patients may have actually had PHTS.…”
Section: 21034mentioning
confidence: 99%